International immigration and domestic out-migrants: Are domestic migrants moving to new jobs or away from immigrants? - Mark Partridge; Dan Rickman; Kamar Ali (European Regional Science Association (ERSA), 2010)
Immigration is one of the most emotional topics in the political arena, which is an issue that has not gone unnoticed by economists. Recent studies usually examine sub-national areas to take advantage of the widely varying local concentrations of immigrants. Yet, there is no consensus on the overall local effects of immigration on migration behavior of domestic residents, although there is consensus that immigration has little influence on local area wages (but there is debate about immigration's influence on national wages). One reason why the regional influence of immigrants is so hard to pin down is the many offsetting economic responses. For example, in response to an influx of recent immigrants, natives and previous immigrants may out-migrate to produce no net effect on total labor supply and, hence, no net effect on local employment or wages. In addition, very little is known about the destinations of native out-migrants. Do they avoid states with greater shares of immigrants, or do they respond to more standard economic measures such as relative growth rates. Using U.S. state-level data, this study examines the effects of recent and past immigration on state-to-state net-migration patterns and on the behavior of domestic state-to-state out-migrants. A key advantage of our migration measures is that we measures of state-to-state migration flows. Thus, we can examine differences across all 1,128 state-to-state migration flows for the lower 48 states. This sample provides considerably more information than the standard approach, which would be analogous to only estimating the 48 state net-migration rates on immigration rates and other control variables. Moreover, state-to-state data allows us to consider whether the domestic out-migrants are moving to states with relatively greater shares of immigrant levels than the origin state, which is an issue that has not been considered in past research. For example, we can answer whether domestic out-migrants are primarily driven by labor market effects or by possible aversion to states with greater shares of immigrants (not just new immigrants).
Keywords: 330